The effects of amoxicillin, cefazolin, and gentamicin antibiotics on the antioxidant system in mouse heart tissues - Savci, Ahmet; Koçpınar, Enver Fehim; Budak, Harun; Ciftci, Mehmet; Sisecioglu, Melda (Bentham Science Publ Ltd, 2020)
Background: Free radicals lead to destruction in various organs of the organism. The improper use of antibiotics increases the formation of free radicals and causes oxidative stress. Objective: In this study, it was aimed to determine the effects of gentamicin, amoxicillin, and cefazolin antibiotics on the mouse heart. Methods: 20 male mice were divided into 4 groups (1st control, 2nd amoxicillin, 3rd cefazolin, and 4th gentamicin groups). The mice in the experimental groups were administered antibiotics intraperitoneally at a dose of 100 mg / kg for 6 days. The control group received normal saline in the same way. The gene expression levels and enzyme activities of SOD, CAT, GPx, GR, GST, and G6PD antioxidant enzymes were investigated. Results: GSH levels decreased in both the amoxicillin and cefazolin groups, while GR, CAT, and SOD enzyme activities increased. In the amoxicillin group, Gr, Gst, Cat, and Sod gene expression levels increased. Conclusion: As a result, it was concluded that amoxicillin and cefazolin caused oxidative stress in the heart, however, gentamicin did not cause any effects.
CIFTCI, MEHMET/0000-0002-1748-3729; KOCPINAR, ENVER FEHIM/0000-0002-6031-4664; Budak, Harun/0000-0002-7371-8959; Sisecioglu, Melda/0000-0002-1127-0570
Keywords: Antibiotic; Antioxidant; Enzyme activity; Gene expression; Oxidative stress; GSH levels